Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Motivasi dan Komitmen Guru - Sabariah Sabariah; Abdul Khair; Muhammad Hizri; Rufi’i Rufi’i; Sulistiami Sulistiami; Agustina Rahmi (An-Nidzam : Jurnal Manajemen Pendidikan dan Studi Islam, 2024)
The aim of the research is to explain and describe transformational leadership as being able to increase teacher motivation and commitment at Madrasah Aliyah Negeri 5 Banjar. The research method is qualitative through a case study approach. Data collection techniques using online questionnaires using Google forms, documentation and observation. Data processing techniques using data collection, reduction, data presentation and drawing conclusions. Data validity techniques with credibility and confirmability. The research results show: (1) transformational leadership: idealized Influence: having a vision and mission, feeling proud, getting attention and trust from teachers. Inspirational Motivation, able to inspire, give an example and motivate teachers to develop. Intellectual Stimulation, increasing teacher creativity and innovation, increasing rationality and problem solving. Individualized Consideration, treating teachers fairly, providing teacher assistance, monitoring and supervision. (2) transformational leadership style is able to increase teacher motivation, such as enthusiasm for carrying out tasks, responsibility, ability to create new ideas. (3) transformational leadership style is able to increase teacher commitment, such as involving teachers in official meetings, training and teacher forums